A Hybrid PSO Applied to the Flexible Job Shop with Transport - Deroussi, Laurent (Swarm Intelligence Based Optimization, 2014)
In this paper, we study the hybridization of particle swarm optimization (PSO) with stochastic local search. This hybrid metaheuristic is applied to a difficult scheduling problem, recently appeared in the literature, the flexible job shop problem with transport. The objective is to determine experimentally the best balance between the exploration ability of PSO and the exploitation ability of the local search. The obtained results show that local search is effectively an important component which permits to significantly improve the basic PSO algorithm.